Młodzież w poszukiwaniu sacrum. Rozważania socjologiczne (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The attitude and relation of modern youth towards the realm of the sacred provide an interesting, though rarely dealt with, subject matter of sociology. The author raises the question of whether this discipline is able to meet the theoretical and empirical challenges regarding the identification of the youth sacred. She draws attention to the ways of understanding the sacred, which revolve around substantive and functional definitions. The modern sacred is subject to strong pressure from post-modern culture, which facilitates its fluidity and hybridity. Young Poles are increasingly becoming ‘absorbers of stimuli’, and neo-tribes cultivate various forms of sensations. The results of quantitative researches, although important for the studied phenomenon, raise some doubts regarding the measurement of features, often unobservable. They urge one to take a deeper reflection on the approaches to the range of designata of the sacred in the context of axiological criteria. Qualitative researches, in turn, describes the phenomenon of the sacred „with understanding”, without abandoning a wider cultural and social background. Both approaches – phenomenological and hermeneutic – seem to be of significant importance in this matter. The experience of the sacred has a personal dimension and it is impossible to fully convey it to others. Triangulation optics provides the opportunity to approach this sphere, which in the case of emerging adulthood implies the acceptance of the risk of losing confidence.